How Accurate is Web-Based Self-Reported Height, Weight, and Body Mass Index in Young Adults? - Pursey, Kirrilly; Burrows, Tracy L; Stanwell, Peter; Collins, Clare E (JMIR Publications, 2014)
BackgroundWeb-based approaches are an effective and convenient medium to deliver eHealth interventions. However, few studies have attempted to evaluate the accuracy of online self-reported weight, and only one has assessed the accuracy of online self-reported height and body mass index (BMI). ObjectiveThis study aimed to validate online self-reported height, weight, and calculated BMI against objectively measured data in young Australian adults. MethodsParticipants aged 18-35 years were recruited via advertisements on social media sites and reported their current height and weight as part of an online survey. They then subsequently had the same measures objectively assessed by a trained researcher. ResultsSelf-reported height was significantly overestimated by a mean of 1.36 cm (SD 1.93; P<.001), while self-reported weight was significantly underestimated by -0.55 kg (SD 2.03; P<.001). Calculated BMI was also underestimated by -0.56 kg/m2 (SD 0.08; P<.001). The discrepancy in reporting resulted in the misclassification of the BMI category of three participants. Measured and self-reported data were strongly positively correlated (height: r=.98, weight: r=.99, BMI: r=.99; P<.001). When accuracy was evaluated by BMI category and gender, weight remained significantly underreported by females (P=.002) and overweight/obese participants (P=.02). ConclusionsThere was moderate to high agreement between self-reported and measured anthropometric data. Findings suggest that online self-reported height and weight can be a valid method of collecting anthropometric data.